Epidemiology of Esophageal Squamous Cell Carcinoma - Abnet, Christian C; Arnold, Melina; Wei, Wen-Qiang (Gastroenterology (New York, N.Y. 1943), 2018)
Esophageal squamous cell carcinoma (ESCC) accounts for about 90% of the 456,000 incident esophageal cancers each year. Regions of high incidence include Eastern to Central Asia, along the Rift Valley in East Africa, and into South Africa. There are many causes of ESCC, which vary among regions. Early studies in France associated smoking cigarettes and heavy alcohol consumption with high rates of ESCC, but these factors cannot explain the high incidence in other regions. We discuss other risk factors for ESCC, including polycyclic aromatic hydrocarbons from a variety of sources, high-temperature foods, diet, and oral health and the microbiome-all require further research. A growing list of defined genomic regions affects susceptibility, but large genome-wide association studies have been conducted with ethnic Chinese subjects only; more studies are called for in the rest of Asia and Africa. ESCC has been understudied, but growing infrastructure in more high-incidence countries will allow rapid progress in our understanding.